Experimental evaluation of the dynamic stiffness of synthetic fibre mooring ropes. (July 2021) - Xu, Sheng; Wang, Shan; Liu, Haixiao; Zhang, Yuming; Li, Linan; Guedes Soares, C.
Abstract: Model tests are conducted to study nonlinear mechanical characteristics of nylon, polyester and high modulus polyethylene. Static tensile and cyclic loading tests are carried out to study the static and dynamic stiffness respectively. Cyclic loading tests with different mean loads and load amplitudes are designed to study the influence of these two parameters on the dynamic stiffness. Based on the measured static results, the fitted expressions for tension-elongation relations of fibre ropes are presented. The empirical expressions developed in previous studies are applied to estimate the dynamic stiffness of synthetic fibre ropes tested in this work, and the estimations are compared with the measured ones. The empirical expression used in this study aims to capture evolution of synthetic rope dynamic stiffness. The extended Kalman filter is applied to identify the parameters of the proposed empirical expressions. The performance of the extended Kalman filter in the parameter identification of the empirical expression for dynamic stiffness is discussed. Furthermore, the influences of observation uncertainties and noise on the outputs of the extended Kalman filter are checked. It is concluded that the extended Kalman filter is able to present reliable and accurate estimations to the parameters of empirical expression for systematic rope dynamic stiffness.